Effects of Biochar on Morphological Characters of Rice Stem. (March 2019) - Xia, Yingjun; Li, Feifei; Song, Qi; Zhang, Jing; Liu, Xupeng; Sun, Lu
Abstract: Biochar has good anatomical structure and physical and chemical properties, and it comes from a wide range of sources. It is of great significance in soil improvement, crop yield increase and environmental improvement. In this study, a japonica rice was used as material. It used four biochar levels to research the effects of biochar on the morphology of rice stem. The results showed that appropriate application of biochar can increase plant height, especially the length of second internode increased significantly. With the increase of biochar, the stem diameter of basal internode (I1) and the second internode (I2) increased significantly, there was an increasing trend of base stem wall thickness, but the difference was not significant. The dry weight per unit length and the dry weight per unit volume will increased with the increase of biochar. The effects of biochar on rice stem strength and lodging resistance should be further studied.